Results confirming the efficacy of oral L-dopa on cortisol secretion in patients being evaluated for suspected growth hormone deficiency - Tarık Kırkgöz; Sezer Acar; Özlem Nalbantoğlu; Behzat Özkan (Trends in Pediatrics, 2023)
Objective: Adrenal insufficiency is a life-threatening disease and therefore, accurate diagnosis and prompt treatment are life-saving. The main purpose of this study was to retrospectively evaluate the serum cortisol levels measured during the L-dopa test in cases suspected GH deficiency and to compare the effect of L-dopa on cortisol secretion with the results of previous studies.